Numerical simulations of materials with micro-structure : limit analysis and homogenization techniques - Lourenço, Paulo B. (2007)
Continuum-based numerical methods have played a leading role in the numerical solution of problems in soil and rock mechanics. However, for stratified soils and fractured rocks, a continuum assumption often leads to difficult parameters to define and over-simplified geometry to be realistic. In such cases, approaches that consider the micro-structure of the material can be adopted. In this paper, two of such approaches are detailed, namely limit analysis incorporating fractures and individual blocks, and elastoplastic homogenization of layered soils.